CAREER WOMEN: BETWEEN GUIDANCE AND DEMANDS IN ISLAMIC STUDIES - Tri Yugo; Dedih Surana (Department Islamic Education, Faculty of Education and Teacher Traning, Universitas Islam Bandung, 2024)
This study discusses the dynamics of the role of career women in an Islamic perspective, specifically how Muslim women balance career demands and religious guidance. In recent decades, the role of women in the workforce has undergone significant changes, with more and more women participating in the public sector. Nonetheless, the challenge of fulfilling domestic responsibilities as wives and mothers by Islamic teachings remains a major concern. This study uses a qualitative approach with a literature study method to analyze religious texts and relevant contemporary literature. The results show that Islam recognizes women's right to work and have a career, but emphasizes the importance of balancing domestic and public roles. Scholars' views on career women vary, from conservative to progressive, but they all agree that women's work should be in line with Sharia principles. Support from the family, especially the husband, is crucial in helping women carry out this dual role. This research provides practical guidance for Muslim women in navigating career challenges in the modern era, as well as contributing to the existing literature by offering a new perspective on how Islam can be a relevant guide in the lives of career women.